New Excited-State Proton Transfer Mechanisms for 1,8-Dihydroxydibenzo[a,h]phenazine - Zhao, Jinfeng; Yao, Hongbin; Liu, Jianyong; Hoffmann, Mark R (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2015)
The excited state intramolecular proton transfer (ESIPT) mechanisms of 1,8-dihydroxydibenzo[a,h]phenazine (DHBP) in toluene solvent have been investigated based on time-dependent density functional theory (TD-DFT). The results suggest that both a single and double proton transfer mechanisms are relevant, in constrast to the prediction of a single one proposed previously (Piechowska et al. J. Phys. Chem. A 2014, 118, 144–151). The calculated results show that the intramolecular hydrogen bonds were formed in the S0 state, and upon excitation, the intramolecular hydrogen bonds between −OH group and pyridine-type nitrogen atom would be strengthened in the S1 state, which can facilitate the proton transfer process effectively. The calculated vertical excitation energies in the S0 and S1 states reproduce the experimental UV–vis absorption and fluorescence spectra well. The constructed potential energy surfaces of the S0 and S1 states have been used to explain the proton transfer process. Four minima have been found on the S1 state surface, with potential barriers between these excited-state minima of less than 10 kcal/mol, which supports concomitant single and double proton transfer mechanisms. In addition, the fluorescence quenching can be explained reasonably based on the proton transfer process.